Time and Metaphor in Emily Dickinson and Ana Blandiana (Papers in Arts and Humanities, 2022)
For so many years on end, my job of teaching some of the most representative American poets has rendered me nostalgic for my own memories of Romanian poetry, whether classic or contemporary. Especially whenever I have had a chance of teaching Emily Dickinson, I fell under the spell of a special affinity between her short striking poems and those of Ana Blandiana, whom I have devotedly admired as an amateur reader, ever since my adolescence. They both have enchanted me by the same playful tone and (seeming) simplicity of poetic expression while conveying metaphysical messages, by means of the most unexpected imagery, which all correspond to Paul Ricoeur's concept of the "living metaphor". This is why my paper title alludes to Ricoeur's celebrated volumes about The Rule of Metaphor and Time and Narrative, in which I have always found reliable support for approaching the best lively books of poetry and narrative of the entire world literature. I hope I will not fail either my guidance or my purpose here.
Keywords: time; grass; death; poetry; passing